Experimental analysis of a novel internally-cooled dehumidifier with self-cooled liquid desiccant. (15th August 2018) - Lun, Wei; Li, Kuining; Liu, Bin; Zhang, Hongji; Yang, Yuxiao; Yang, Cheng
Abstract: With respect to air dehumidification, an internally-cooled dehumidifier is more efficient than an adiabatic dehumidifier. In the present study, a new method to control the increase in the temperature of the liquid dehumidifier solution was presented. A self-cooled liquid desiccant solution was defined and prepared. Anhydrous ethanol was added into the lithium chloride (LiCl) aqueous solution as the vaporizable coolant to control the increase in the temperature of the solution. A working hypothesis for the self-cooled solution dehumidification was established with a main feature wherein the heat exchangers in conventional internally-cooled dehumidifier were replaced by using self-cooled liquid desiccant solution. Its performance was compared and experimentally investigated. An environmental chamber and a visible experimental setup were established. Experimental results under different operating conditions were obtained. The performance indices including moisture removal rate and dehumidification efficiency were analysed. When compared with conventional LiCl liquid desiccant solution, the current analysis indicated that the self-cooled solution is superior with respect to the above performance indices. Graphical abstract: Image 1 Highlights: A new method to control the increase in the temperature of a liquid desiccant is presented. A self-cooled liquid desiccant solution is defined and prepared. An environmental chamber and a visible experimental setup are established. The performance indices in different operating conditions are experimentally investigated. A superior dehumidification performance of the self-cooled solution is verified.